Characterization of Water-Soluble Intermediates from Slow Pyrolysis of Cellulose at Low Temperatures - Yu, Yun; Liu, Dawei; Wu, Hongwei (American Chemical Society, 2012)
This study reports the presence of both sugar and anhydro-sugar oligomers of a wide range of degrees of polymerization (1–10) as water-soluble intermediates in the solid residues produced from cellulose slow pyrolysis at low temperatures (100–350 °C) and a holding time of 30 min. These sugar and anhydro-sugar oligomers appear to be important precursors of volatiles formation during cellulose pyrolysis. Even at very low pyrolysis temperatures (e.g., 100 °C), sugar oligomers are found in the water-soluble intermediates. As the breakage of glycosidic bonds within cellulose chains is unlikely to take place under such low-temperature conditions, the results suggest that such sugar oligomers are likely to be produced from the short glucose chain segments that are hinged with crystalline cellulose via weak bonds (e.g., hydrogen bonds) in amorphous portions of microcrystalline cellulose. As the pyrolysis temperature increases, a wide range of anhydro-sugar oligomers start to appear while the sugar oligomers start to decrease.At temperatures <270 °C, water-soluble intermediates are dominantly >78% based on total carbon) contributed by sugar oligomers, anhydro-sugar oligomers, and a large amount of partially decomposed sugar-ring-containing oligomers, i.e., PDSRCOs, but such contributions decrease substantially as the pyrolysis temperature increases to 300 °C. At higher pyrolysis temperatures (e.g., 325 °C), all sugar-ring-containing oligomers completely disappear, accompanied by substantial weight loss of cellulose. Together with those from the pyrolysis of sugar model compounds, such results further suggest that the production of an hydro-sugar oligomers are more likely due to the homolytic or heterolytic cleavage of glycosidic bonds of crystalline or amorphous cellulose within microcrystalline cellulose, rather than direct dehydration of sugar oligomers products within the intermediate phase.